Autoimmunity as a sequela to obesity and systemic inflammation - Kwiat, Victoria R.; Reis, Gisienne; Valera, Isela C.; Parvatiyar, Kislay; Parvatiyar, Michelle S. (Frontiers in Physiology, 2022)
The rising prevalence of obesity presents a world-wide challenge as it is associated with numerous comorbidities including cardiovascular disease, insulin resistance and hypertension. Obesity-associated illnesses are estimated to cause nearly 4 million deaths globally per year, therefore there is a critical need to better understand associated pathogenesis, identify new therapeutic targets, and develop new interventions. Emerging data identify a key role for chronic inflammation in mediating obesity related disease states and reveal higher incidence of autoimmune disease development. Of the multiple potential mechanisms linking obesity and autoimmunity, the strongest link has been shown for leptin, a hormone secreted at high levels from obese white adipose tissue. Numerous studies have demonstrated that leptin enhances activation of both arms of the immune system, while its absence protects against development of autoimmunity. Other potential newly discovered mechanisms that contribute to autoimmune pathogenesis are not directly connected but also associated with obesity including sustained platelet activation, gut dysbiosis, and aging. Here we review how obesity instigates autoimmunity, particularly in the context of immune cell activations and adipokine secretion.